Autophagy in Tenebrio molitor Immunity: Conserved Antimicrobial Functions in Insect Defenses - Jo, Yong Hun; Lee, Jung Hee; Patnaik, Bharat Bhusan; Keshavarz, Maryam; Lee, Yong Seok; Han, Yeon Soo (Frontiers in Immunology, 2021)
The yellow mealworm beetle (Tenebrio molitor) has been exploited as an experimental model to unravel the intricacies of cellular and humoral immunity against pathogenic infections. Studies on this insect model have provided valuable insights into the phenotypic plasticity of immune defenses against parasites and pathogens. It has thus been possible to characterize the hemocoelic defenses of T. molitor that rely on the recognition of non-self-components of pathogens by pattern recognition receptors (PRRs). The subsequent signaling cascade activating pathways such as the NF-κB controlled by Toll and IMD pathways lead to the synthesis of antimicrobial proteins (AMPs), onset of hemocyte-driven phagocytosis, and activation of the prophenoloxidase cascade regulating the process of melanization. Nevertheless, the activation of autophagy-mediated defenses of T. molitor against the facultative intracellular gram-positive bacterium Listeria monocytogenes provides clear evidence of the existence of a crosstalk between autophagy and the IMD pathway. Moreover, the identification of several autophagy-related genes (Atgs) in T. molitor RNA Sequencing and expressed sequence tag databases has contributed to the understanding of the autophagy-signaling cascade triggered by L. monocytogenes challenge. Providing further evidence of the cross-talk hypothesis, TmRelish has been shown to be required not only for regulating the synthesis of AMPs through the PGRP-LE/IMD pathway activation but also for the expression of Atgs in T. molitor larvae following L. monocytogenes challenge. Notably, L. monocytogenes can stimulate the T. molitor innate immune system by producing molecules recognized by the multifunctional PRR (TmPGRP-LE), which stimulates intracellular activation of the IMD pathway and autophagy. Considering the conservation of autophagy components involved in combating intracellular pathogens, it will be interesting to extrapolate a dynamic crosstalk model of immune activation. This review summarizes the most significant findings on the regulation of autophagy in T. molitor during L. monocytogenes infection and on the role of the innate immunity machinery, including the NF-κB pathway, in the control of pathogenic load. Key words: Insect; Beetle; Yellow mealworm; Tenebrio molitor; Listeria monocytogenes; Autophagy signaling cascade; Expressed sequence tag (EST); RNA-seq